Under Voltage and Over Voltage Protection of Electrical Equipment - A Review - Dipali Kale; Bhushan Kadam; D. B Pardeshi (International Journal of Electrical Power and Machine Systems, 2024)
In our modern, digitally-driven world, the seamless operation of electrical equipment is paramount, spanning industries, households, and infrastructure. However, the reliability of these vital assets is inextricably linked to the quality of electrical power supplied to them. Voltage fluctuations, specifically under voltage and over voltage events, pose significant threats to the integrity and functionality of electrical equipment. This review paper undertakes a comprehensive exploration of under voltage and over voltage protection systems, shedding light on their pivotal role in mitigating power quality challenges. It delves into the multifaceted causes, classifications, and the wide-reaching consequences of these voltage anomalies, addressing power quality issues from grid instabilities to load imbalances. Moreover, this paper presents a meticulously designed protection system synthesized from an extensive review of the literature. This system stands as the central guardian of the electrical network, ensuring the stability and quality of power supplied to connected equipment through vigilant monitoring and rapid corrective actions. As we navigate through this review, it becomes evident that the reliability and durability of electrical equipment are intrinsically linked to the quality of the power they receive. By addressing the multifaceted challenges presented by under voltage and over voltage conditions, this paper aims to make a significant contribution to the broader mission of securing the uninterrupted and secure operation of electrical equipment. It reinforces the foundations of a modern, efficient, and resilient electrical infrastructure well-equipped to face the dynamic power quality challenges of our digital age.
Keywords: Circuit Operation; Electrical Circuits; Equipment Safety; Protection Systems; Voltage Anomalies; Voltage Protection; Zener Diodes; power quality